MAKNA SIMBOL ARTEFAK PADA PROSESI MAPPATUDANG ARAJANG MELALUI MEDIA FOTOGRAFI - Mathar, Hasbulllah (Jurnal Dakwah Tabligh, 2022)
This study is a study that discusses the concept of culture that exists in human life. This study aimed to find out the meaning of the artifact symbols in the Mappatudang Arajang procession in Bone Regency through the media of photography. To achieve the objectives of this study, the use of descriptive qualitative research methods and semiotic research approaches. Data collection techniques were carried out through observation, in-depth interviews, and documentation. The results showed three meanings in the symbols of artifacts in the Mappatudang Arajang procession through the media of photography. The first is as a symbol of courage. The second is as a symbol of life. the third is as a form of respect for their ancestors. And the Fourth is considedered a symbol of ideology. These three meanings have been implemented into people’s lives in Bone Regency.